Erwerbskarrieren in Ostdeutschland – 20 Jahre nach der Deutschen Einheit und darüber hinaus - Johannes Geyer; Viktor Steiner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2010)
– The unemployment rate in East Germany has been almost twice as high as in West Germany since unification. At the same time, employment subject to social security contributions decreased markedly. We analyse how these developments are reflected in the careers of birth cohorts born between 1937 and 1971. German reunification affected these cohorts differently as they were between 53 and 29 years of age when the wall came down and thus in different stages of their careers. To account for this, we estimate cohort effects in employment careers for men and women differentiated by skill group on the basis of the Socio-Economic Panel (SOEP). Our projection of future careers, based on the estimated cohort effects, shows a massive decline in cumulated full-time employment over the life-cycle and a dramatic increase of unemployment for younger birth cohorts. Given that the estimation of cohort effects and the projection of future careers are based on a negative labour market development in East Germany since unification, we also analyse an alternative scenario characterized by an improvement of future employment careers of younger birth cohorts.
Keywords: 330; Arbeitslosigkeit; sozialversicherungspflichtige Arbeitnehmer; Sozioökonomisches Panel; Berufsverlauf - Prognose; Bildungsniveau; Beschäftigungsform; Qualifikationsniveau; Arbeitsmarktentwicklung; erwerbstätige Frauen; erwerbstätige Männer; Ostdeutschland; Bundesrepublik Deutschland